Evolution of The Education Curriculum in Indonesia - M Topit Hidayat; Surya Suryadi; Nuri Latifannisa; Sefni Novita Sari; Rino Rino (Yayasan Keluarga Guru Mandiri, 2025)
The Indonesian national curriculum has changed several times, more than ten times to be precise. These changes are logically the result of science learning on political issues, government systems, social culture, economics, and technological science in public society. This research aims to determine the development of the curriculum that has been implemented in Indonesia from a historical perspective. The method used in this research is qualitative method. Collecting research data uses documentation and library techniques. This study identifies key findings from related research and examines curriculum development in Indonesia using a systematic literature review (SLR) based on the PRISMA approach. The results of data collection were then analyzed using qualitative descriptive analysis techniques. The results of this research show that the history of the curriculum that has been implemented in Indonesia from a comparative study perspective can be traced from the curriculum before independence (curriculum during the VOC, Dutch East Indies, and Japanese Occupation) to the curriculum after independence, including those from 1947, 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006, 2013, and freedom curriculum. The continuous evolution of the curriculum highlights the government's commitment to improving education and ensuring that it remains relevant in an ever-changing world.